دراسة اقتصادية لإنتاج محصول البصل بمحافظة الغربية - السيد، عزام عبداللطيف; مبارك، محمد عبدالستار علي; قابيل، مفيدة السيد محمد; حربي، هالة شوقي عبدالعليم (الجمعية المصرية للإقتصاد الزراعي, 2022)
يتلخص الهدف الرئيسي من هذا البحث في كيفية التغلب على معوقات إنتاج وتسويق محصول البصل لتشجيع المزارعين على الاستمرار في إنتاجه والعمل على زيادة المساحات المزروعة وزيادة الكميات المنتجة منه، وزيادة الكميات المصدرة، ومن ثم زيادة حصيلة الصادرات من النقد الأجنبي والتي يمكن أن تعود على الاقتصاد القومي بالفائدة، وهذا يتطلب دراسة وتقدير الكفاءة الاقتصادية لأهم العناصر الإنتاجية المؤثرة على إنتاج هذا المحصول. وكذا تقدير أهم المقاييس الاقتصادية في إنتاج محصول البصل وقد تبين من نتائج البحث أن عنصري المساحة المزروعة (X1) والعمل الآلي- موتور رش (X5) يؤثران في إنتاج محصول البصل في الفئة الحيازية الأولى. وعنصري العمل الآلي- جرار (X3) والعمل الآلي -ري بماكينة الري (X4) يؤثران في إنتاج محصول البصل في الفئة الحيازية الثانية. أما عنصر العمل البشري (X2) فيؤثر في إنتاج محصول البصل في الفئة الحيازية الثالثة. وعنصر المبيدات (X9) يؤثر في إنتاج المحصول في الفئات الحيازية الثلاث، في حين يؤثر عنصر السماد الآزوتي (X7) في إنتاج محصول البصل في الفئتين الحيازيتين الثانية والثالثة. وبدراسة المقاييس الاقتصادية تبين أن متوسط كل من صافي العائد، الفائض الحدي، العائد على الجنيه المستثمر ونسبة هامش الربح للمنتج يزداد كلما انتقلنا من الفئة الحيازية الأدنى إلى الفئة الحيازية الأعلى ويرجع ذلك إلى وفورات السعة. The main objective of this research is how to overcome the obstacles to the production and marketing of the onion crop to encourage farmers to continue producing it and work to increase the cultivated areas and increase the quantities produced from it, Increasing the exported quantities, and then increasing the export earnings of foreign exchange, which can bring benefit to the national economy, This requires studying and estimating the economic efficiency of the most important productive factors affecting the production of this crop. As well as estimating the most important economic measures in the production of the onion crop. It was found from the results of the research that the two components of the cultivated area (X1) and the automatic work-motor spraying (X5) affect the production of the onion crop in the first tenure category. And the two elements of automated work- tractor (X3) and automated work- irrigation with irrigation machine (X4) affect the production of the onion crop in the second holding category. As for the human labor component (X2), it affects the production of the onion crop in the third holding category. And the pesticide component (X9) affects the production of the crop in the three tenure categories, while the nitrogen fertilizer component (X7) affects the production of the onion crop in the second and third tenure categories. By studying the economic measures, it was found that the average net return, marginal surplus, return on the invested pound and the product’s profit margin ratio increases as we move from the lowest holding category to the higher holding category, due to capacity savings.
Keywords: الكفاءة الاقتصادية -- الإنتاج الزراعي -- محصول البصل -- مصر